2012
DOI: 10.1111/j.1432-2277.2012.01443.x
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesvirus-6 infections in kidney, liver, lung, and heart transplantation: review

Abstract: Summary Human herpesvirus‐6 (HHV‐6), which comprises of HHV‐6A and HHV‐6B, is a common infection after solid organ transplantation. The rate of HHV‐6 reactivation is high, although clinical disease is not common. Only 1% of transplant recipients will develop clinical illness associated with HHV‐6 infection, and most are ascribable to HHV‐6B. Fever, myelosuppression, and end‐organ disease, including hepatitis and encephalitis, have been reported. HHV‐6 has also been associated with various indirect effects, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 104 publications
0
78
0
Order By: Relevance
“…25 In addition to encephalitis, HHV-6 reactivation has been associated with an increased risk of GVHD, delayed engraftment, cytopenia, opportunistic infections and fever. 19,[26][27][28][29][30][31] There is still a considerable uncertainty on the clinical significance of HHV-6 reactivation, and routine testing for HHV-6 is not currently performed at most transplant centers. The purpose of our study was to conduct a systematic review of the literature and a meta-analysis to clarify the relationship between CBT and HHV-6 reactivation and assess the pooled prevalence of encephalitis among CBT patients.…”
Section: Introductionmentioning
confidence: 99%
“…25 In addition to encephalitis, HHV-6 reactivation has been associated with an increased risk of GVHD, delayed engraftment, cytopenia, opportunistic infections and fever. 19,[26][27][28][29][30][31] There is still a considerable uncertainty on the clinical significance of HHV-6 reactivation, and routine testing for HHV-6 is not currently performed at most transplant centers. The purpose of our study was to conduct a systematic review of the literature and a meta-analysis to clarify the relationship between CBT and HHV-6 reactivation and assess the pooled prevalence of encephalitis among CBT patients.…”
Section: Introductionmentioning
confidence: 99%
“…Viral reactivation can result in delayed transplant engraftment and severe complications up to lethal encephalitis (5). Furthermore, transplantation of solid organs-including kidney, liver, lung, and heart-results in high rates of HHV-6 reactivation, although only 1% of transplant recipients were found to develop severe complications (6). There is no acute disease known to be caused by HHV-6A, but recent studies have suggested potential involvement in multiple sclerosis (MS) aggravation (7).…”
mentioning
confidence: 99%
“…125 Symptoms and signs attributed to HHV-6 include fever, rash, cytopenia, interstitial pneumonitis, hepatitis but a definite causeand-effect relationship with HHV-6 is often lacking. 126,127,128 The virus may have immunosuppressive effects through interaction with CMV or by affecting the immune system directly. An association between invasive fungal infections and HHV-6 has been suggested.…”
Section: Herpes Simplex Virus and Varicella Zoster Virusmentioning
confidence: 99%
“…Currently available serologic tests available are of limited value because of high seroprevalence in the general population and also because transplant recipients receiving immunosuppressive medication may not mount a serologic response. 128 Sensitive polymerase chain reaction-based detection of HHV-6 may detect latent virus and overestimate the presence of infection. Antiviral agents active against CMV are also active against HHV-6, including ganciclovir, foscarnet, and cidofovir.…”
Section: Herpes Simplex Virus and Varicella Zoster Virusmentioning
confidence: 99%